Comparison of visual and computerised antenatal cardiotocography in the prevention of perinatal morbidity and mortality. A systematic review and meta-analysis. (August 2021) - Baker, H.; Pilarski, N.; Hodgetts-Morton, V.A.; Morris, R.K.
Highlights: We have found no significant difference between antenatal cCTG and vCTG in preventing perinatal mortality. The previous 2015 Cochrane Review included an incorrect event rate from one RCT. The evidence base for comparison of vCTG and cCTG has considerable limitations. A prospective representative observational study is warranted to address these. Abstract: Introduction: Antenatal cardiotocography (CTG) is used to monitor fetal well-being. There are two methods: visual (vCTG) or computerised (cCTG). An earlier Cochrane review compared the effects of both approaches on maternal and fetal outcomes. The objective of this systematic review was to update this search and identify studies not included in the Cochrane review. Materials and methods: MEDLINE, EMBASE, CINAHL and MIDIRS databases were searched up to February 2021. We included randomised controlled trials (RCT) and non-randomised studies (NRS) of pregnant women receiving antenatal CTG with comparison of cCTG to vCTG and clinical outcomes. The Cochrane Risk of Bias Tool and Joanna Briggs Institute Critical Appraisal Checklist were used for quality assessment. Data is presented as risk ratios with 95% confidence intervals and I 2 is used as the statistical measure of heterogeneity. Results: Three RCTs and three NRS were included. Meta-analysis of RCTs demonstrated a non-significant reduction in all-cause perinatal mortality (RR 0.23 [95%CI 0.04–1.30]), preventable perinatal mortality excluding congenital anomalies (RR 0.27 [95% CI 0.05–1.56]) and cesarean section (RR 0.91 [95%CI 0.68–1.22]). All RCTs included high-risk women and had a high risk of bias. There was one antenatal stillbirth across the three RCTs (n = 497). The NRS were at high-risk of bias and statistical analysis was not possible due to heterogeneity. Individual findings suggest reduced investigation and better prediction of neonatal outcomes with cCTG. Conclusions: There is a non-significant reduction in perinatal mortality with cCTG. Despite no clear reduction in perinatal mortality and morbidity with cCTG, it is objective and may reduce time spent in hospital and further investigations for women.